2022
DOI: 10.36778/jesya.v5i1.655
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompetensi Dan Pelatihan Terhadap Tingkat Kelulusan Sertifikasi Guru Dan Dampaknya Pada Kinerja Guru Pada Sma Negeri Di Bangkinang Kota

Abstract: This study aims to determine the effect of competence and training on the passing rate of teacher certification and its impact on teacher performance at SMA Negeri in Bangkinang Kota. The population in this study were all teachers of SMAN 1 Bangkinang Kota and teachers of SMAN 2 Bangkinang Kota which were known to be 112 teachers. In this study, the entire population was sampled, so the number of samples in this study amounted to 112 respondents, the sampling technique was called the saturated census technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Studi ini konsisten dengan studi yang dilakukan oleh (Zulfahmi et al, 2022). Menurut temuan studi tersebut, semakin tinggi tingkat kompetensi guru yang ditunjukkan, semakin tinggi pula persentase kandidat yang berhasil menyelesaikan persyaratan sertifikasi guru.…”
Section: Upaya Meningkatkan Kinerja Guru Melalui Peningkatan Kompeten...unclassified
See 1 more Smart Citation
“…Studi ini konsisten dengan studi yang dilakukan oleh (Zulfahmi et al, 2022). Menurut temuan studi tersebut, semakin tinggi tingkat kompetensi guru yang ditunjukkan, semakin tinggi pula persentase kandidat yang berhasil menyelesaikan persyaratan sertifikasi guru.…”
Section: Upaya Meningkatkan Kinerja Guru Melalui Peningkatan Kompeten...unclassified
“…Sertifikasi guru berusaha untuk meningkatkan proses dan hasil pembelajaran, kesejahteraan guru, dan kelayakan guru untuk tugas mengajar profesional. (Zulfahmi et al, 2022).…”
unclassified
“…According to Fathussyakir & Meutia (2022), SMK teachers in Bima City's salaries have a favourable and statistically significant impact on their students' academic outcomes. According to Zulfahmi et al (2022), certification rates have been shown to correlate with student outcomes; more certified teachers lead to better test scores for their students. According to research by Darinto et al ( 2022), instructors at SMK Wahid Hasyim Glagah showed considerable improvement in output after receiving partial financial remuneration.…”
Section: The Effect Of Financial Compensation Performance Assessment ...mentioning
confidence: 99%